الصعوبات التي تواجه أستاذ التعليم الإبتدائي اثناء انجازه لحصة التربية البدنية والرياضية من وجهة نظر معلمي التعليم الابتدائي - مسوس بلال (My University, 2023)
.......................................................................................................abstract..................................................................................... Study Title: Difficulties faced by the primary education teacher during the completion of the physical education and sports class. • Objective of the study: - Explaining the importance of the role of the absence of specialization for the primary education teacher in physical education and sports is one of the reasons that hinder the activation of the physical education and sports class in primary education. - Highlighting the most important difficulties facing the primary education teacher during the completion of physical education and sports classes in terms of the child's motor gains. - Finding out whether the lack of sports structures and facilities and the lack of pedagogical means are among the reasons that hinder the activation of the physical education and sports quota in primary education. • Study hypotheses: - The absence of specialization for the primary education teacher in physical education and sports is one of the reasons that hinder the activation of the physical education and sports class in primary education. - There are difficulties facing the primary education teacher during the completion of physical education and sports classes in terms of the child's motor gains. - The lack of sports structures and facilities and the lack of pedagogical means are among the reasons that hinder the activation of the physical education and sports quota in primary education. • Field study procedures: Sample: The sample was taken from eighty-one (35) primary school teachers of the betting department - Souk Ahras - Temporal domain:It is known methodologically that the researcher determines the time period in which he went to the field, and in the current study, the research group conducted a survey study on primary school teachers - Souk Ahras , and this was limited to the period from 20/02/2023 to 05/04/2023. Spatial area: The study was carried out at the primary school level of the betting department - Souk Ahras– • Methodology used:The descriptive survey method was used. • Tools used:We relied in our study on a questionnaire form. • Findings:The following results have been reached: - The absence of specialization for the primary education teacher in physical education and sports is one of the reasons that hinder the activation of the physical education and sports class in primary education. - There are difficulties facing the primary education teacher during the completion of physical education and sports classes in terms of the child's motor gains. - The lack of sports structures and facilities and the lack of pedagogical means are among the reasons that hinder the activation of the physical education and sports quota in primary education. - Physical and athletic soil plays an important role in the growth of the pupil at this stage. • Conclusions and suggestions: - The need to prepare a teacher specialized in physical education and sports in primary school, so it is not reasonable to enter the world through its wide door today and we do not employ specialists to implement the program. - The need to assign the teaching of physical and sports education at the primary stage to specialists from university institutes. - Work on the establishment and preparation of spaces of fields and playgrounds for the physical education and sports class, while providing conditions of safety and prevention. .........................................................................................................................ملخص الدراسة ................................................................................................... عنـوان الدراسـة: الصعوبات التي تواجه استاذ التعليم الابتدائي اثناء انجازه لحصة التربية البدنية والرياضية. • هـدف الدراسـة: - تبيين أهمية دور غياب التخصص لأستاذ التعليم الابتدائي في التربية البدنية والرياضية يعد من الاسباب التي تعيق تفعيل حصة التربية البدنية والرياضية في مرحلة التعليم الابتدائي. - ابراز أهم الصعوبات التي تواجه استاذ التعليم الابتدائي اثناء انجازه لحصص التربية البدنية والرياضية من حيث المكتسبات الحركية للطفل. - معرفة ما ان كان نقص الهياكل والمنشآت الرياضية وقلة الوسائل البيداغوجية يعد من الاسباب التي تعيق تفعيل حصة التربية البدنية والرياضية في مرحلة التعليم الابتدائي. • فرضـيات الدراسـة: - غياب التخصص لأستاذ التعليم الابتدائي في التربية البدنية والرياضية يعد من الاسباب التي تعيق تفعيل حصة التربية البدنية والرياضية في مرحلة التعليم الابتدائي. - هناك صعوبات تواجه استاذ التعليم الابتدائي اثناء انجازه لحصص التربية البدنية والرياضية من حيث المكتسبات الحركية للطفل. - نقص الهياكل والمنشآت الرياضية وقلة الوسائل البيداغوجية يعد من الاسباب التي تعيق تفعيل حصة التربية البدنية والرياضية في مرحلة التعليم الابتدائي. • إجـراءات الدراسـة الميدانيـة : العينـة : تتكون من (35) معلم من معلمي المدارس الابتدائية لدائرة المراهنة - سوق أهراس - المجـال الـزماني : من المعروف منهجيا أن يحدد الباحث الفترة الزمنية التي نزل فيها إلى الميدان وفي الدراسة الحالية قام الباحث باجراء دراسة إستطلاعية على معلمي المدارس الابتدائية لدائرة المراهنة - سوق أهراس ، وقد إقتصر هذا على الفترة الممتدة من 20/02/2023 إلى غاية 05/04/2023. المجال المكاني: تمت الدراسة على مستوى المدارس الابتدائية لدائرة المراهنة - سوق أهراس- والبالغ عددهم 09 ابتدائيات • المنهـج المستخـــدم : تم إستخدام المنهج الوصفي المسحي . • الأدوات المستعملـــة :إعتمدنا في دراستنا على إستمارة إستبيان . • النتائج المتـوصل إلـيها : لقد تم التوصل إلى النتائج التالية : - غياب التخصص لأستاذ التعليم الابتدائي في التربية البدنية والرياضية يعد من الاسباب التي تعيق تفعيل حصة التربية البدنية والرياضية في مرحلة التعليم الابتدائي. - هناك صعوبات تواجه استاذ التعليم الابتدائي اثناء انجازه لحصص التربية البدنية والرياضية من حيث المكتسبات الحركية للطفل. - نقص الهياكل والمنشآت الرياضية وقلة الوسائل البيداغوجية يعد من الاسباب التي تعيق تفعيل حصة التربية البدنية والرياضية في مرحلة التعليم الابتدائي. • إستخـلاصات واقتراحــات: - ضرورة إعداد مدرس مختص في التربية البدنية والرياضية في المدرسة الابتدائية فلا يعقل أن ندخل العالم من بابه الواسع اليوم ونحن لا نوظف المتخصصين لتطبيق البرنامج. - ضرورة إسناد تدريس مادة التربية البدنیة والریاضیة في الطور الابتدائي إلى متخصصین من خریجي المعاهد الجامعية. - العمل على انشاء وتهيئة الفضاءات من ميادين وملاعب خاصة بحصة التربية البدنية والرياضية، مع توفير شروط الآمن والوقاية. .........................................................................................................résumé......................................................................... Titre de l'étude : Difficultés rencontrées par l'enseignant du primaire lors de la réalisation du cours d'éducation physique et sportive. • Objectif de l'étude: - Expliquer l'importance du rôle de l'absence de spécialisation pour l'enseignant du primaire en éducation physique et sportive est l'une des raisons qui entravent l'activation de la classe d'éducation physique et sportive dans l'enseignement primaire. - Mettre en évidence les difficultés les plus importantes rencontrées par l'enseignant du primaire lors de la réalisation des cours d'éducation physique et sportive en termes de gains moteurs de l'enfant. - Rechercher si le manque de structures et d'équipements sportifs et le manque de moyens pédagogiques sont parmi les raisons qui entravent l'activation du quota d'éducation physique et sportive dans l'enseignement primaire. • Hypothèses d'étude : - L'absence de spécialisation de l'enseignant du primaire en éducation physique et sportive est l'une des raisons qui entravent l'activation de la classe d'éducation physique et sportive dans l'enseignement primaire. - Il existe des difficultés rencontrées par l'enseignant du primaire lors de la réalisation des cours d'éducation physique et sportive au niveau des gains moteurs de l'enfant. - Le manque de structures et d'équipements sportifs et le manque de moyens pédagogiques sont parmi les raisons qui entravent l'activation du quota d'éducation physique et sportive dans l'enseignement primaire. • Procédures d'étude sur le terrain : Echantillon : L'échantillon a été prélevé auprès de quatre-vingt-un (35) enseignants du primaire du département des paris - Souk Ahras - Domaine temporel : Il est connu méthodologiquement que le chercheur détermine la période de temps pendant laquelle il est allé sur le terrain, et dans la présente étude, le groupe de recherche a mené une enquête auprès des enseignants du primaire - Souk Ahras, et cela s'est limité à la période du 20/02/2023 au 05/04/2023. Zone spatiale : L'étude a été réalisée au niveau de l'école primaire du département des paris - Souk Ahras– • Méthodologie utilisée : La méthode d'enquête descriptive a été utilisée. • Outils utilisés : Nous nous sommes appuyés dans notre étude sur un formulaire de questionnaire. • Constatations : Les résultats suivants ont été atteints : - L'absence de spécialisation de l'enseignant du primaire en éducation physique et sportive est l'une des raisons qui entravent l'activation de la classe d'éducation physique et sportive dans l'enseignement primaire. - Il existe des difficultés rencontrées par l'enseignant du primaire lors de la réalisation des cours d'éducation physique et sportive au niveau des gains moteurs de l'enfant. - Le manque de structures et d'équipements sportifs et le manque de moyens pédagogiques sont parmi les raisons qui entravent l'activation du quota d'éducation physique et sportive dans l'enseignement primaire. - Le sol physique et sportif joue un rôle important dans la croissance de l'élève à ce stade. • Conclusions et suggestions : - La nécessité de préparer un enseignant spécialisé en éducation physique et sportive à l'école primaire, il n'est donc pas raisonnable d'entrer dans le monde par sa large porte aujourd'hui et nous n'employons pas de spécialistes pour mettre en œuvre le programme. - La nécessité de confier l'enseignement de l'éducation physique et sportive au niveau primaire à des spécialistes des instituts universitaires. - Travailler à l'aménagement et à l'aménagement d'espaces de terrains et d'aires de jeux pour la classe d'éducation physique et sportive, tout en assurant des conditions de sécurité et de prévention.
دراسة ميدانية على مستوى ابتدائيات دائرة المراهنة– سوق أهراس –